Integrating Payor-Segregated Outpatient Obstetrics and Gynecology Care Models: The Patient Perspective - Chesnokova, Arina E.; Apple, Annie; Kaur, Karampreet; Schachter, Allison; Clement, Elizabeth A.; Schapira, Marilyn M.; Sonalkar, Sarita; Polite, Florencia G.; Vinekar, Kavita; James, Abike T.; Hamm, Rebecca F. (American Journal of Perinatology, 2025)
Significant racial and ethnic disparities in maternal morbidity and mortality as well as gynecologic outcomes persist in the United States. The role of ambulatory care in obstetrics and gynecology (OBGYN), particularly in facilities that separate resident and attending care along payor (and de facto racial) lines, remains unclear. This study examines patient perspectives on payor-segregated health care delivery in an academic medical center (AMC) and opinions on possible integration.This is a qualitative study conducted at a single AMC with payor-segregated resident and attending outpatient sites. Interviews focused on patient perception of experience and value in outpatient OBGYN care, perspectives on the segregated care model, and attitudes about integration. Patients participated in a 30-minute semistructured interview with recruitment continuing until thematic saturation was reached (October 2022–August 2023). Interviews were coded using an integrated approach with grounded theory; 12% of transcripts were double-coded (k = 0.86).We interviewed 26 patients (16 from resident, 10 from attending site). Patients prioritized practical aspects such as clinic proximity and quality of clinician interaction. Most were unaware of the payor-segregated clinic system and disapproved upon learning about it. Opinions varied on topics of telehealth and continuity, indicating diverse patient needs. Notably, minoritized patients valued race and class concordance in clinical spaces. Patients generally supported care integration, conditional upon the preservation of aspects of care they valued.Successful OBGYN care integration requires meeting individual needs while ensuring diversity, safety, and community-oriented care, alongside access and convenience. Incorporating patient voices is crucial for aligning services with expectations and improving patient experiences.
Keywords: obstetrics and gynecology; ambulatory care delivery; health equity; payment and financing; graduate medical education; patient voice